Relative abundance of 'Candidatus Tenderia electrophaga' is linked to cathodic current in an aerobic biocathode community. Issue 1 (11th July 2017) - Malanoski, Anthony P.; Lin, Baochuan; Eddie, Brian J.; Wang, Zheng; Hervey, W. Judson; Glaven, Sarah M.
Summary: Biocathode microbial communities are proposed to catalyse a range of useful reactions. Unlike bioanodes, model biocathode organisms have not yet been successfully cultivated in isolation highlighting the need for culture‐independent approaches to characterization. Biocathode MCL ( Marinobacter, Chromatiaceae, Labrenzia ) is a microbial community proposed to couple CO2 fixation to extracellular electron transfer and O2 reduction. Previous metagenomic analysis of a single MCL bioelectrochemical system (BES) resulted in resolution of 16 bin genomes. To further resolve bin genomes and compare community composition across replicate MCL BES, we performed shotgun metagenomic and 16S rRNA gene (16S) sequencing at steady‐state current. Clustering pooled reads from replicate BES increased the number of resolved bin genomes to 20, over half of which were > 90% complete. Direct comparison of unassembled metagenomic reads and 16S operational taxonomic units (OTUs) predicted higher community diversity than the assembled/clustered metagenome and the predicted relative abundances did not match. However, when 16S OTUs were mapped to bin genomes and genome abundance was scaled by 16S gene copy number, estimated relative abundance was more similar to metagenomic analysis. The relative abundance of the bin genome representing ' Ca . Tenderia electrophaga' was correlated with increasing current, further supporting the hypothesis that this organism is the electroautotroph. Abstract : Results presented here show a positive correlation between the relative abundance of " Candidatus Tenderia electrophaga" and the amount of current at the cathode, substantiating its role as an electroautotroph. This finding is original and significant because to date there are no reports of previously uncharacterized marine bacteria directly linked to autotrophic extracellular electron transfer (EET) in a mixed microbial population enriched from the environment."